From concept to practice: The IFS model of ICAR-IARI and its impact on smallholder farming - Dam, Adrita; Singh, Rajiv Kumar; Rathore, Sanjay Singh; Kumar, Pramod (Indian Farming, 2025)
Indian agriculture, largely dependent on small and marginal farmers, faces significant challenges such as limited resources, resource degradation, and declining profitability. The Integrated Farming System (IFS) offers a viable solution by integrating various agricultural components—crop production, livestock, aquaculture, and agroforestry—to create a resource-efficient, cyclical system that minimizes waste and enhances productivity. ICAR-IARI’s IFS model, designed for a 1-hectare irrigated area, includes nine components: crop production, pisciculture, duckery, poultry, apiary, agroforestry, composting unit, biogas plant, and dairy. This model optimizes land use, improves soil health, and ensures continuous income. The feasibility analysis highlights the dairy module as the most profitable with the highest Net Present Worth (NPW) and a strong Benefit-Cost Ratio (B:C), while the poultry and apiary modules also show significant financial viability. The IFS model supports food security, enhances nutritional security, and creates employment opportunities. By recycling resources efficiently and managing them holistically, IFS provides a resilient and sustainable agricultural solution that addresses the needs of small and marginal farmers, promotes biodiversity, and ensures economic stability.